NUTRITIONAL VALUE AND CHEMICAL COMPOSITION OF MEAT (British Journal of Global Ecology and Sustainable Development, 2024)
In this regard, the technology of processing meat products today, and increasing the production of canned meat are topical issues of the day, and meat and meat products are considered very important food products, as they contain vitamins and minerals. The taste is good.